Developing a Resilient Early Childhood Education Curriculum: A Disruption-Resiliency Continuum Theory - Garma, Vernel A. (Southeast Asia Early Childhood Journal, 2025)
Understanding a resilient early childhood curriculum is vital in ensuring educational continuity amid disruptions. This study aims to develop a theory describing a disruption-resilient early childhood education curriculum continuum. A deductive axiomatic approach to theory development was utilized, where scholarly literature serves as the foundational basis for generating a theory. An extensive review of related literature was conducted to analyze the data collected from available research studies. The theory was developed based on the readings and discussions about early childhood education, curriculum development, and educational resilience. Axioms were generated to come up with propositions. The following propositions are posed: 1.) An early childhood education curriculum that focuses on essential knowledge and skills for learners is resilient to disruptions. 2.) An early childhood education curriculum that is flexible in design and delivery is resilient to disruptions. 3.) An early childhood program with strong parent-teacher collaboration contributes to curriculum resilience during disruptions. 4.) Professional development for educators contributes to curriculum resilience. The propositions concluded that the continuum of a disruption-resilient early childhood education curriculum comprises three interconnected components: essential knowledge and skills, flexible design and delivery, and an activated support system. This theory presents significant applications for ensuring the continuity of quality early childhood education, even in the face of disruptions.